BAKTERI M2 PENGHASIL PHB (Polyhydroxybutirate) YANG DIISOLASI DARI PULAU LAKI, KEPULAUAN SERIBU - Dyah Supryati (Jurnal Teknologi Lingkungan, 2010)
Polyhydroxybutirate Producing Bacteria M2 Isolated From Pulau Laki, KepulauanSeribu. PHB is one of very important material for production of biodegradable plastic,and physiologically it is important electron sink in anaerobic-aerobic process. PHB accumulating bacteria M2 was isolated from mangrove of Pulau Laki, Kepulauan Seribu.The bacteria were able to produce PHB from glucose, acetate, and sucrose .Strain M2 was produced PHB (79.9% of biomass) by using acetate as sole carbon sources. The strain was also able to grow at 3 % to 5 % with a doubling time of 10.9 and 21.04 hours and specific growth rate (0.0633 h-1 and 0.0328 h-1). The ability of Strain M2 to produce PHB and its salinity tolerance implying that this strain is not only importance for PHB production but also ecologically importance microbe.Key word: PHB accumulating bacteria, marine, salinity tolerance